Kajian Lokasi dalam Konteks Arkeologi Industri: : Studi Kasus PG Karangsuwung, Cirebon 1920-1943 - Dharussalam, Robby (Jurnal Konservasi Cagar Budaya, 2023)
The sugar industry was very profitable during the Dutch East Indies colonial period due to favorable geographical conditions in Indonesia for sugar cane cultivation. However, not all areas were suitable for establishing sugar factories. PG Karangsuwung is a historical site that represents the prosperity of the sugar industry during that period and is being studied to determine an ideal location for a sugar factory. The study involved three stages: data collection through literature and field observations, data processing through macro and micro spatial analysis using GIS, and interpretation through contextual analysis of the environment around the factory. The results of the study indicate that PG Karangsuwung has a focus on labor and raw material sources and is located in an integrated arrangement for the sugar industry.